2014
DOI: 10.1111/and.12332
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin protects testicular and spermatological damages induced by cisplatin in rats

Abstract: The clinic usage of cisplatin, an anticancer drug, is limited due to it has many side effects in many systems and organs. In this context, it was aimed to investigate the protective effect of hesperidin, a citrus flavonoid, on testicular and spermatological damages induced by cisplatin in rats. The rats were randomly divided into four groups. The first group was kept as a control. In the second groups, cisplatin was given at the single dose of 7 mg kg(-1) intraperitoneally. In the third group, hesperidin was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 33 publications
7
55
0
Order By: Relevance
“…[1,2] However, its ototoxicity, nephrotoxicity, myelotoxicity, and gastrointestinal toxicity, and serious side effects involving neurologic, hematologic, and reproductive system restrict its clinical use. [3,4] Multiple number of studies have indicated the roles of reactive oxygen radicals (ROSs), and oxidative stress (OS) on reproductive toxicity of cisplatin. [4] Though oxygen is indispensable for the survival of living organisms, during its metabolism, extremely reactive intermediate products which are known as the sources of free radicals are formed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1,2] However, its ototoxicity, nephrotoxicity, myelotoxicity, and gastrointestinal toxicity, and serious side effects involving neurologic, hematologic, and reproductive system restrict its clinical use. [3,4] Multiple number of studies have indicated the roles of reactive oxygen radicals (ROSs), and oxidative stress (OS) on reproductive toxicity of cisplatin. [4] Though oxygen is indispensable for the survival of living organisms, during its metabolism, extremely reactive intermediate products which are known as the sources of free radicals are formed.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Multiple number of studies have indicated the roles of reactive oxygen radicals (ROSs), and oxidative stress (OS) on reproductive toxicity of cisplatin. [4] Though oxygen is indispensable for the survival of living organisms, during its metabolism, extremely reactive intermediate products which are known as the sources of free radicals are formed. Reactive molecules released during conversion of foods into energy are called as free radicals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HP has radical clearance and anti-inflammatory effects [15,16] . It has been reported that Hesperidin significantly reduces lipid peroxidation in testicular tissue, leads to positive effects on sperm parameters and biochemical parameters, as well as provides improvements in epididymal functions [14,17] .…”
Section: Introductionmentioning
confidence: 99%